Volume 7: Turbomachinery, Parts a and B 2009
DOI: 10.1115/gt2009-59706
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study for the Effect of Vaned Diffuser Leading Edge on the Noise Generated From a Centrifugal Fan

Abstract: This paper studies a novel vaned diffuser with inclined leading edge to reduce the fan noise. The aerodynamic performances and sound pressure level (SPL) of the centrifugal fan with five different diffusers were measured in an anechoic chamber, and the inclined angles of the five diffusers are 45°, 60°, 120°, 135° and 150°, respectively. The flow coefficient of the fan varies from 0.037 to 0.14, the rotational speed ranges from 20000rpm to 35000rpm. The test results show that, by using diffuser vanes with incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Mao and Qi (2009) considered the noise of the blades is mainly originated from the vicinity of the trailing edge. Zhang et al (2009a, b) verified that the leading edge of the diffuser vane plays an important role in the impeller‐diffuser interaction through the experimental studies. Gu et al (2007) believed that the movement and shatters of the eddies also disturbed the airflow, which makes the level of pressure pulsations and noise rise.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Mao and Qi (2009) considered the noise of the blades is mainly originated from the vicinity of the trailing edge. Zhang et al (2009a, b) verified that the leading edge of the diffuser vane plays an important role in the impeller‐diffuser interaction through the experimental studies. Gu et al (2007) believed that the movement and shatters of the eddies also disturbed the airflow, which makes the level of pressure pulsations and noise rise.…”
Section: Introductionsupporting
confidence: 58%
“…However, the excessive energy losses, vibrations and noise generated by the fans have become a serious problem. Especially the fan noise, which consists of rotational and eddy noises at high rotational speed, is unbearable (Li et al , 2002; Zhang et al , 2009a, b; Yang et al , 2008; Xi et al , 2002). Therefore, finding the causes is the fundamentals of finding an appropriate solution.…”
Section: Introductionmentioning
confidence: 99%
“…However, one of important issues, namely the influence of the diffuser leading edge on the noise of centrifugal fans, has not been considered. Previous works by the authors [11] showed that the inclined leading edge vaned diffuser (ILEVD) could reduce the fan noise. The objective of this article is to find a good geometric shape of the diffuser leading edge to reduce the noise of the centrifugal fan.…”
Section: Introductionmentioning
confidence: 99%
“…The geometry of the diffuser plays an important role in the noise generation; hence, the redesign of the vane diffuser may help reduce the interaction noise. The authors' previous work 6,7 showed that the inclined leading edge vane diffuser could reduce the fan noise and improve the fan performance.…”
Section: Introductionmentioning
confidence: 99%